2005
DOI: 10.1158/1055-9965.epi-04-0749
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Testicular Germ Cell Cancer in Relation to Variation in Maternal and Offspring CytochromeP450 Genes Involved in Catechol Estrogen Metabolism

Abstract: The incidence of testicular germ cell carcinoma (TGCC) is highest among men ages 20 to 44 years. Exposure to relatively high circulating maternal estrogen levels during pregnancy has long been suspected as being a risk factor for TGCC. Catechol (hydroxylated) estrogens have carcinogenic potential, thought to arise from reactive catechol intermediates with enhanced capability of forming mutation-inducing DNA adducts. Polymorphisms in maternal or offspring genes encoding estrogenmetabolizing enzymes may influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 59 publications
4
25
2
2
Order By: Relevance
“…A study by Starr et al found an inverse association between the CYP1A2 variant rs762551 and TGCT risk [46], consistent with the current study's findings with CYP1A1. Although the current study did not investigate CYP1A2 polymorphisms directly, CYP1A1 and CYP1A2 are in close proximity and in strong LD.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Starr et al found an inverse association between the CYP1A2 variant rs762551 and TGCT risk [46], consistent with the current study's findings with CYP1A1. Although the current study did not investigate CYP1A2 polymorphisms directly, CYP1A1 and CYP1A2 are in close proximity and in strong LD.…”
Section: Discussionsupporting
confidence: 92%
“…Recent evidence supports an association of TGCT with polymorphisms in these genes: we and others have reported an association with CAG/GGN repeat length of the androgen receptor gene (Giwercman et al 2004, Garolla et al 2005 and with FSH receptor gene polymorphisms (Ferlin et al 2008a), and an association with some maternal and/or offspring hormonemetabolizing genes of the cytochrome P450 family (CYP1A1, CYP1A2, CYP3A4, and CYP3A5) has been suggested (Starr et al 2005, Figueroa et al 2008.…”
Section: Introductionsupporting
confidence: 57%
“…Associations with TGCT have been found with mutations in the androgen receptor gene (Garolla et al 2005), different lengths of the CAG and GGC repeats in exon 1 of the androgen receptor gene which modulate the sensitivity of the receptor to androgens (Giwercman et al 2004, Garolla et al 2005, polymorphisms of the FSH receptor gene which modulate FSH sensitivity (Ferlin et al 2008a), and polymorphisms in cytochrome P450 genes involved in estrogen metabolism (Starr et al 2005, Figueroa et al 2008. With regards to Endocrine-Related Cancer (2010) 17 17-25 www.endocrinology-journals.org these latter genes, an association between TGCT and CYP1A2 (rs762551), CYP3A4 (rs2740574), and CYP3A5 (rs776746) gene polymorphisms was found by one study (Starr et al 2005), whereas an association with polymorphisms in CYP1A1 (rs4886605 and rs2606345) gene was found by another one (Figueroa et al 2008). We did not include CYP3A4 and CYP3A5 genes in our screening, nor we included SNPs rs4886605 and rs2606345 in CYP1A1 and rs762551 in CYP1A2; therefore, we were unable to confirm such associations.…”
Section: Discussionmentioning
confidence: 99%
“…Поскольку местом взаимодействия субстратов І типа с гемопротеином является гидрофобный участок апофермента [18,19], то весьма вероятно, что в микросомальной мембране в формировании его принимают участие фосфолипиды. Свободнорадикальные состояния последних могут придавать апоферменту цитохрома Р450 определенные конформации и тем самым понижать N-деметилазную активность последнего, что приводит к компенсаторной активации n-гидроксилирования анилина [20,21].…”
Section: рисунокunclassified